Evaluation of Synergic Effects of Molybdenum Disulfide Treatment and Near Infrared Radiation on Human Mesenchymal Stem Cells: MoS2 and NIR effects on mesenchymal stem cells - Omidi Farzin, Alireza; Arjmand, Babak; Asri , Nastaran; Razzaghi, Zahra; Razi, Farideh; Bandarian, Fatemeh; M Robati, Reza; Rezaei, Mitra; Vafaee, Reza; Rahnamay Farnood, Parnia (Journal of Lasers in Medical Sciences, 2026)
Introduction: Molybdenum disulfide (MoS2), as an anticancer reagent, can absorb near-infrared (NIR) wavelengths in phototherapy. In the present study, the synergic effect of MoS2 (in nanostructure) and NIR radiation on human mesenchymal stem cells (hMSCs) was evaluated via protein-protein interaction (PPI) network analysis. Methods: Gene expression profiles of hMSCs were extracted from the Gene Expression Omnibus (GEO) database and analyzed via PPI network analysis. The validity of findings was assessed via the Kaplan-Meier Plotter. Results: FN1, ACTA2, CCL2, CXCL8, FBN1, and LEP genes were selected as hub genes among 121 recognized differentially expressed genes (DEGs) as the targeted genes by the synergic effects of MoS2 and NIR radiation. Kaplan-Meier Plotter analysis demonstrated that FN1 suppression by MoS2 and NIR radiation can significantly increase the overall survival of patients with gastric cancer, lung cancer, ovarian cancer, and myeloma. Conclusion: In conclusion, findings indicate that the anticancer property of MoS2 is intensified in the condition of NIR radiation. Therefore, MoS2 is a suitable photosensitizer reagent in photodynamic therapy.